The scientific notation of the population is .
It is required to find the solution.
Scientific notation is a way of writing very large or very small numbers. A number is written in scientific notation when a number between 1 and 10 is multiplied by a power of 10. Scientific Notation is the expression of a number n in the form a∗10b. where a is an integer such that 1≤|a|<10. and b is an integer too.
Given :
The given number is
20,612,439
in scientific notation is
Move the decimal point so that there is seven non-zero digit to the left.
Hence, the scientific notation of the population is .
Learn more about scientific notation here:
#SPJ2
Answer:
2.0612439 x 10 to the 7th power
Step-by-step explanation:
Answer:
7.89
Step-by-step explanation:
Subtract on calculator bro!
Answer:
its 7.63
Step-by-step explanation:
Answer:
A=lw
A=3×3
A=9
Explanation
Answer:
46.5
Step-by-step explanation:
Solution
A=a+b
2h=5.3+13.3
2·5=46.5
Answer:
x = -3 and y = 1.
Step-by-step explanation:
The given system of equations is:
-x + 3y = 6 ---(1)
-10x - 3y = 27 ---(2)
To solve this system of equations, we can use the method of elimination or substitution.
Method 1: Elimination
To eliminate the variable y, we can add equations (1) and (2) together:
(-x + 3y) + (-10x - 3y) = 6 + 27
Simplifying the equation gives us:
-11x = 33
Dividing both sides of the equation by -11, we get:
x = -3
Now, we can substitute this value of x into either equation (1) or (2) to find the value of y. Let's use equation (1):
-x + 3y = 6
Substituting x = -3, we have:
-(-3) + 3y = 6
Simplifying the equation gives us:
3 + 3y = 6
Subtracting 3 from both sides of the equation, we get:
3y = 3
Dividing both sides of the equation by 3, we have:
y = 1
Therefore, the solution to the system of equations -x + 3y = 6 and -10x - 3y = 27 is x = -3 and y = 1.
Method 2: Substitution
Let's solve the system of equations using the substitution method.
From equation (1), we can express x in terms of y:
x = 6 - 3y ---(3)
Substitute this expression for x into equation (2):
-10(6 - 3y) - 3y = 27
Simplifying the equation gives us:
-60 + 30y - 3y = 27
Combining like terms, we have:
27y = 87
Dividing both sides of the equation by 27, we get:
y = 3
Now, substitute this value of y into equation (3):
x = 6 - 3(3)
Simplifying the equation gives us:
x = 6 - 9
x = -3
Therefore, the solution to the system of equations -x + 3y = 6 and -10x - 3y = 27 is x = -3 and y = 3.
Both methods lead to the same solution, which is x = -3 and y = 1.